2013
DOI: 10.1556/oh.2013.29558
|View full text |Cite
|
Sign up to set email alerts
|

Importance of the 11β-hydroxysteroid dehydrogenase enzyme in clinical disorders

Abstract: A glükokortikoidok szabályozzák a szénhidrát-és aminosav-anyagcserét, modulálják az immunrendszer működé-sét és a stresszre adott válaszreakciókat. Elégtelen, illetve fokozott szekréciójuk jellegzetes kórképeket okoz. A szervezet glükokortikoidhormon-ellátottsága mellett az utóbbi évtizedben előtérbe került az adott szövetekben loká-lisan képződő glükokortikoidok patofi ziológiai szerepének kutatása. A lokális glükokortikoidellátottság egyik kulcsenzime a sejtek endoplazmatikus reticulumában elhelyezkedő 11-β-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 48 publications
(102 reference statements)
0
3
0
1
Order By: Relevance
“…These findings indicated that DEGs may have a significant impact on regulating TME and influencing the prognosis of ccRCC. Since The HSD11B1 gene encodes the type 1 isoform of 11-β-hydroxysteroid dehydrogenase, which converts glucocorticoids into the active form, which plays an important role in the regulation of metabolic syndrome and immune response [ 21 ]. Further analyses were carried out on HSD11B1 expression profile.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These findings indicated that DEGs may have a significant impact on regulating TME and influencing the prognosis of ccRCC. Since The HSD11B1 gene encodes the type 1 isoform of 11-β-hydroxysteroid dehydrogenase, which converts glucocorticoids into the active form, which plays an important role in the regulation of metabolic syndrome and immune response [ 21 ]. Further analyses were carried out on HSD11B1 expression profile.…”
Section: Discussionmentioning
confidence: 99%
“…Eventually, a predictive biomarker, hydroxysteroid 11-beta dehydrogenase-1 (HSD11B1) was selected. The HSD11B1 gene encodes the type 1 isoform of 11-β-hydroxysteroid dehydrogenase, which converts glucocorticoids into the active form, which plays an important role in the regulation of cell proliferation, differentiation and immune response [ 21 , 22 ]. Proliferative phenotypes induced by high expression of HSD11B1 are associated with poor cancer prognosis [ 23 ].…”
Section: Introductionmentioning
confidence: 99%
“…It is apparent in rodent and human studies, where there is a greater understanding of the physiological roles of GCs, that chronic overexposure to GCs (whether during development or in the adult) can result in multiple and wide‐ranging adverse effects (as reviewed by Almawi et al 2002; Girod & Brotman, 2004; Walker, 2007; McDonough et al 2008; Feldman et al 2013). These studies highlight the importance of homeostatic regulation through the processes of biosynthesis and catabolism.…”
Section: Discussionmentioning
confidence: 99%
“…A CTON CTOL-á való átalakulást a 11-βHSD1 enzim katalizálja, főként a májban, gonádokban, zsírszövetben, agyban és csontban. [14] A TEST DHTT-ná alakul át az 5-alfa-reduktáz enzim hatására a szervezet perifériás szöveteiben, a prosztatában, herékben, a májban és az ováriumban. […”
Section: Egyéb Szervek Szteroid Hormon Termeléseunclassified